2022
DOI: 10.1002/maco.202112900
|View full text |Cite
|
Sign up to set email alerts
|

Cerium citrate as ecologically friendly corrosion inhibitor for AA7075 alloy

Abstract: The corrosion behaviour of high-strength AA7075 aluminium alloy in NaCl solution, without and in the presence of environmentally friendly corrosion inhibitors (Ce-chloride and Ce-citrate) in low concentrations (<0.5 mM), was analysed. The degree of precipitation of the solid solution of AA7075 alloy was determined by measuring the electrical conductivity, while the surface morphology and appearance of intermetallic compounds before and after corrosion testing were analysed by SEM/EDS method. The general corros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The authors of this paper recently analyzed the inhibitory properties of Ce‐citrate in neutral NaCl solution on aluminum alloy AA7075. [ 34 ] Ce‐citrate has shown very effective corrosion inhibitory properties on this aluminum alloy. However, due to the presence of oxide passive film (Al 2 O 3 ) and intermetallic inclusions of different compositions, and so on, the corrosion and electrochemical behavior of the aluminum alloys differ significantly from the behavior of the steel.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this paper recently analyzed the inhibitory properties of Ce‐citrate in neutral NaCl solution on aluminum alloy AA7075. [ 34 ] Ce‐citrate has shown very effective corrosion inhibitory properties on this aluminum alloy. However, due to the presence of oxide passive film (Al 2 O 3 ) and intermetallic inclusions of different compositions, and so on, the corrosion and electrochemical behavior of the aluminum alloys differ significantly from the behavior of the steel.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Also, the various cerium salts were tested, and it was found that Ce acetate has the best protective ability on the 7xxx series aluminum alloy. [24] Other cerium salts were also tested, such as citrates, [26] phosphates, [27] sulfates, [24,28,29] perchlorates, [24] and nitrates. [28,30,31] The Ce acetate inhibitory effect of the 7xxx series aluminum alloy has recently been investigated in detail.…”
mentioning
confidence: 99%
“…In the following period, various inorganic cerium salts were tested to improve the inhibitory effect of cerium, such as nitrates, [9][10][11] perchlorates, [12] and sulfates. [12,13] Also organic cerium salts, such as diphenyl phosphate, [14] formate, [15] acetate, [13,[15][16][17] citrate, [18] and propionate [15] were analyzed.…”
mentioning
confidence: 99%